Constitutional Development in the Yukon Territory: Perspectives on the "Epp Letter" - Smyth, Steven (ARCTIC, 1999)
The 1978 Yukon Territorial election was the first to be contested by all three territorial political parties. The Yukon Territorial Progressive Conservative Party, which won the election, quickly demanded constitutional change, and received a positive response from the federal Progressive Conservative government in 1979. The Minister of Indian and Northern Affairs, Jake Epp, acceded to the Yukon Government's request and issued a letter of instruction to the federally appointed Commissioner, Ione Christensen. He ordered her to divest herself of her portfolio responsibilities and not participate in executive decision making. Mrs. Christensen immediately resigned, stating that she did not want the role of a de facto Lieutenant Governor. Her resignation triggered a debate in the Yukon legislature and the media over whether the Territory was moving "too far, too fast" toward provincial status. Academics and politicians have also debated whether the changes effected by the "Epp letter" were significant and irreversible, or merely a "sop" to assuage local sentiments. The anomaly of the Yukon's constitutional status in Canada is raised as a consequence of this debate. L'élection de 1978 dans le Territoire du Yukon a été la première à faire l'objet d'une contestation par les trois partis politiques du Territoire. Le parti Progressiste-Conservateur du Yukon, qui avait remporté l'élection, ne tarda pas à réclamer un changement constitutionnel et, en 1979, reçu une réponse positive du gouvernement fédéral Progressiste-Conservateur. Jake Epp, ministre des Affaires indiennes et du Nord canadien, accéda à la demande du gouvernement du Yukon et fit parvenir au Commissaire nommé par le fédéral, Ione Christensen, une lettre de directives. Il lui ordonnait de se défaire des responsabilités rattachées à son portefeuille et de ne pas participer aux prises de décision administratives. Madame Christensen démissionna immédiatement de son poste, déclarant qu'elle ne voulait pas d'un rôle de lieutenant-gouverneur de fait. Sa démission ...